Biochemical and clinical deficiency is uncommon in African immigrants despite a high prevalence of low vitamin D: the Africans in America study - Thoreson, C. K.; Chung, S. T.; Ricks, M.; Reynolds, J. C.; Remaley, A. T.; Periwal, V.; Li, Y.; Sumner, A. E. (Osteoporosis international, 2015)
Summary African ancestry is associated with low vitamin D levels but high bone density. Fifty percent of African immigrants had low vitamin D levels, but <10 % had evidence of deficiency. The value of providing vitamin D supplementation to African immigrants without evidence of deficiency needs to be determined. Introduction The Endocrine Society and Institute of Medicine (IOM) have concluded from studies in largely white populations that 25(OH)D is necessary for bone health. However, their definition of vitamin D insufficiency differs. The Endocrine Society recommends a 25(OH)D threshold of <30 ng/mL. The IOM uses a lower threshold of 25(OH)D of <20 ng/mL. As African ancestry is associated with decreased 25(OH)D but increased bone mineral density (BMD), the applicability of these thresholds to Africans is unknown. Therefore, we examined in African immigrants the relationship of 25(OH)D to parathyroid hormone (PTH) and BMD. Methods One hundred eighty-six African immigrants(69 % male, age 38 ± 10 (mean ± SD), range 20–64 years) living in metropolitan Washington, DC, were enrolled. BMD was determined from whole-body dual-energy X-ray absorptiometry (DXA) scans. Decreased BMD required T-scores ≤−1.0. The threshold for low 25(OH)D was the concentration of 25(OH)D at which PTH became suppressed. This is known as the inflection point. Biochemical deficiency required low 25(OH)D and PTH of >65 pg/mL. Clinical deficiency required low 25(OH)D and T-scores ≤−1.0. Results 25(OH)D <30 and <20 ng/mL occurred in 83 and 46 % of African immigrants, respectively. PTH inversely correlated with 25(OH)D ( r = −0.31, P = 0.002). The inflection point occurred at a 25(OH)D concentration of 20 ng/mL. Biochemical and clinical deficiency occurred in only 8 and 3 % of immigrants, respectively. Conclusion As PTH became suppressed at 25(OH)D of 20 ng/mL, the 25(OH)D <20 ng/mL threshold for insufficiency may apply to African immigrants. However, ~50 % of African immigrants have 25(OH)D <20 ng/mL, but only <10 % had evidence of deficiency. The value of providing vitamin D supplementation to the large number of African immigrants with 25(OH)D <20 ng/mL and no detectable evidence of deficiency needs to be determined.